Positive effects of neuromuscular shoulder exercises with or without EMG-biofeedback, on pain and function in participants with subacromial pain syndrome – A randomised controlled trial. (October 2019) - Juul-Kristensen, Birgit; Larsen, Camilla Marie; Eshoj, Henrik; Clemmensen, Trine; Hansen, Anders; Bo Jensen, Peter; Boyle, Eleanor; Søgaard, Karen
Abstract: Background: The aim was to investigate the effect of Electromyography (EMG)-biofeedback guided exercises (BIONEX) on shoulder pain and function in participants with subacromial pain syndrome (SPS). Methods: Twenty-five women and 24 men (19–67 years), diagnosed with SPS, were randomised to BIONEX or the same exercises without EMG-biofeedback (NEX). Primary outcome was shoulder pain during the past 7 days (Numeric Pain Rating Scale (NPRS)). Secondary outcomes included self-reported (Disability of Arm Shoulder and Hand (DASH), Oxford Shoulder Score (OSS)), and measured shoulder function (surface EMG from upper trapezius, lower trapezius and serratus anterior) in mean and ratios of % of maximum voluntary EMG (%MVE) and onset time (msec), during arm tasks with 0, 1 and 3 kg. Results: There was no group difference (BIONEX versus NEX) in changed shoulder pain (NPRS, mean difference 0.18 (95% CI. −1.56; 1.19)), self-reported or measured shoulder function. Both groups, however, showed significant within-group improvements on self-reported outcomes (NPRS, DASH, OSS), only clinically relevant on NPRS (BIONEX 2.23 (SD 2.47); NEX 2.04 (SD 2.29)). Conclusion: BIONEX and NEX were both effective in reducing pain to a clinically relevant level, while EMG-biofeedback did not make a difference. The current neuromuscular shoulder exercise protocol is recommended.